2008
DOI: 10.1017/s1138741600004662
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Version of the Flow State Scale

Abstract: The purpose of this research was to examine the psychometric properties of a Spanish translation of the Flow State Scale (FSS; Jackson & Marsh, 1996). This instrument is used to assess the Flow State in participants of physical activity, although it can be adapted to other contexts (such as work, educational contexts, etc.). This construct can be considered the optimal psychological state to carry out an activity, being closely related to motivation and personal enjoyment (Csikszentmihalyi, 1997). A sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 31 publications
2
21
0
12
Order By: Relevance
“…The first aim of the present study was to investigate the factorial structure of the Shared Flow Scale developed on the basis of the Spanish version of the Dispositional Flow Scale (García Calvo et al, 2008). CFA showed that the best and most parsimonious model was represented by a single second-order factor and nine first-order factors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first aim of the present study was to investigate the factorial structure of the Shared Flow Scale developed on the basis of the Spanish version of the Dispositional Flow Scale (García Calvo et al, 2008). CFA showed that the best and most parsimonious model was represented by a single second-order factor and nine first-order factors.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, the effects are the loss of selfconsciousness (7), the distortion of time (8) and the autotelic experience (9) . Existing research has confirmed the validity of a nine-dimensional model of individual flow (Delle Fave & Bassi, 2009;García Calvo, Jiménez, Santos-Rosa, Reina, & Cervelló, 2008;Jackson & Eklund, 2002). Importantly, flow is a multifaceted experience, and according to the existing evidence distinct facets of flow are correlated.…”
Section: Collective Gatherings Collective Effervescence and Shared Flowmentioning
confidence: 88%
“…Este estudio ha contrastado la estructura factorial de flujo en el caso de actividades físico-deportivas, comprobándose que la experiencia de flujo compartido se estructura en las nueve dimensiones teóricas, al igual que sucede con los estudios del flujo individual (García-Calvo et al, 2008). El modelo factorial de segundo orden mostró los mejores índices de ajuste en comparación con los modelos alternativos, congruentemente con otros estudios (Jackson y Eklund, 2002, 2004Moneta, 2012).…”
Section: Conclusionesunclassified
“…The assessment was based on the Flow State Scale or FSS [23], which measures quantitatively the flow level achieved by people participating in physical activities in general; however, this scale has been adapted to other contexts such as work, learning and computing environments [24]. In this study, we used a Spanish version of the scale translated by Calvo et al, which is a coherent and valid equivalent of its English version [25]. The FSS consists of 36 Likert-type items/questions that go from 1 (strongly agree) to 10 (strongly disagree).…”
mentioning
confidence: 99%
“…Table 7 shows a mapping between the flow dimensions and the FSS question numbers. The full set of questions is available in [23,25]. The sample included 38 people, 19 men and 19 women, aged from 19 to 56 years old, with under and graduate degrees, all clinically healthy, that did not participate in the previous experiment.…”
mentioning
confidence: 99%